Pengaruh Kualitas Layanan dan Harga terhadap Kepuasan Pelanggan - Bali, Santi Handayani; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the effect of service quality and price on customer satisfaction at Supermarket Laris Bawen. The focus of this study is to understand the extent to which service quality and price can increase satisfaction and build customer loyalty. The approach used is a quantitative method with a survey technique through a questionnaire distributed to customers. Data were analyzed using multiple linear regression to test the relationship between variables. The results showed that service quality, which includes employee friendliness, speed of service, and comfort of facilities, has a positive and significant effect on customer satisfaction. Competitive prices, comparable to the benefits received, as well as discount and promotion programs also contribute to increasing customer satisfaction and loyalty. Reliability tests show that all research instruments have a Cronbach's Alpha value above 0.7, which indicates a good level of reliability. This study concludes that improving service quality and implementing appropriate pricing strategies are key factors in increasing customer satisfaction and competitiveness of supermarkets. The practical implications of these findings suggest that supermarket management needs to prioritize employee training to improve friendliness and service, as well as develop competitive pricing strategies and attractive promotions to retain customers. However, this study has limitations in terms of limited regional scope and customer characteristics, so the results cannot be generalized widely. Further research is recommended to include additional variables and a wider range of respondents to obtain a more comprehensive understanding